Plant diversity and composition at three Imperata grasslands in Bogor, Katingan, and Kupang, Indonesia - didi usmadi; JOKO RIDHO WITONO; RENI LESTARI; DIDIK WIDYATMOKO; MAHAT MAGANDHI; IYAN ROBIANSYAH; ARIEF NOOR RACHMADIYANTO; DANANG WAHYU PURNOMO; RIZMOON NURUL ZULKARNAEN; REZA RAMDAN RIVAI; HENDRA HELMANTO; ANGGA YUDAPUTRA; FRISCA DAMAYANTI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Usmadi D, Witono JR, Lestari R, Widyatmoko D, Magandhi M, Robiansyah I, Rachmadiyanto AN, Purnomo DW, Zulkarnaen RN, Rivai RR, Helmanto H, Yudaputra A, Damayanti F. 2020. Plant diversity and composition at three Imperata grasslands in Bogor, Katingan, and Kupang, Indonesia. Biodiversitas 21: 2804-2813. Imperata grassland is among the largest proportions of marginal lands in Indonesia. Despite the dominance of Imperata cylindrica grass, certain plant species are able to compete and live together with this species, suggesting window of opportunity that the grasslands can be restored. Yet, the existing diversity and composition of plants in Imperata grasslands may vary due to differences in climatic and soil conditions. This study aims to determine the plant diversity and composition at three Imperata grasslands in Bogor, Katingan, and Kupang, Indonesia. Data were collected using systematic sampling by establishing quadratic observation plots with size of each plot was 1 x 1 m2. The total number of species found in Imperata grasslands in those three study sites was 81 species, belonging to 68 genera and 30 families. In the Bogor site, the dominant species were Imperata cylindrica, Ageratum conyzoides, and Phyllanthus niruri, while in the Katingan site was dominated by I. cylindrica, Scleria ciliaris, and Cyanthillium cinereum and in the Kupang site was dominated by I. cylindrica and Tridax procumbens. The Imperata grassland in Bogor had low species richness, moderate species diversity, the abundance distribution of each species tends to be uniform, and the occurred species did not tend to dominate. The Katingan and Kupang Imperata grasslands had low species richness, low species diversity, the abundance distribution of each species tends to be uneven, and were more dominated by I. cylindrica. Controlling abundance of I. cylindrica is required in those three research sites in order to stimulate the growth of other plant species, which is in turn to maintain and restore biodiversity.